Epistemological Paradigms in Positivism, Interpretivism, and Action Research in Educational Research: A Literature Review - Mustofa, Mustofa (Journal of Office Administration : Education and Practice, 2024)
This study elaborates the three prominent paradigms in educational research: positivism, interpretivism, and action research. I epistemologically elucidate these paradigms through literature reviews, offering insights and critiques. Positivism emphasizes empirical explanation, typically focusing on observable behavior. Interpretivism highlights contextual understanding. Action research emphasizes participation and dialectical processes. The result of this study does not claim that there is only one best approach to educational research. However, it provides a philosophical overview of each paradigm.